Morphological, teratogenic and behavioral evaluations of Gelidium spinosum methanol extract on zebrafish embryos - Warsi, Warsi; Jaswir, Irwandi; Ahmed, Qamar Uddin; Mahfudh, Nurkhasanah; Mohd. Nawi, Mohamed Sufian; Rohman, Abdul; Khatib, Alfi (Pensoft Publishers, 2024)
Gelidium spinosum is an edible red seaweed from the family Gelidiaceae with possibility to be developed. The potential medical benefits of G. spinosum have been established, yet adequate empirical research on its toxicity is still lacking. Hence, the present work was aimed to examine the toxicity of G. spinosum methanol extract (GsME) on zebrafish (Danio rerio) embryos and to identify the phytoconstituents using gas chromatography-mass spectrometry (GC-MS) analysis. Results of this study showed that GsME induced morphological defects in zebrafish embryos, including reduction in eye size and body length. Moreover, yolk sac size and mortality were increased in zebrafish embryos exposed to GsME in a dose-dependent manner. GsME at high concentrations triggered teratogenic effects in zebrafish embryos such as decrease in heartbeat/minute, lack of pigmentation, lack of somite, structural deformity, pericardial oedema, and yolk oedema. The LC50 and EC50 of GsME were < 100 mg/L, which classified as a harmful category. The teratogenic index of GsME was found to be > 1, indicating its teratogenic attribute. Additionally, GsME exerted behavioral effects i.e. significantly lower total distance of movement and slower swimming speed of zebrafish embryos. GC-MS analysis of GsME was confirmed the presence of amino acid, phenolics, carboxylic acids, reducing sugars, saturated fatty acids and brominated saturated fatty acid in the extract. It suggesting that compounds of 13-bromotetradecanoic acid, palmitic acid, and stearic acid containing in GsME were contributed to the toxic effects.